Amelogenesis Imperfecta. The Likelihood of Genetic Transmission to the Next Generation in Costa Rican Families - Murillo Knudsen MDSc, Gina; Silva de la Fuente MQC, MSc, Sandra; Mata Martínez DDS, Mariana; Esquivel Hidalgo DDS, María José (Odovtos - International Journal of Dental Sciences, 2015)
Amelogenesis Imperfecta describes a group of structural anomalies of dental enamel whose inheritance pattern may be dominant or recessive autosomal, or sex-linked pattern to X chromosome. It also can be linked to spontaneous genetic mutation called as novo mutation. Members of seven Costa Rican families, affected and not affected by Amelogenesis Imperfecta, were studied with the objective of determining the probability of future generations manifesting the condition in dental enamel. Subjects were referred by students and faculty members, of the postgraduate program in pediatric dentistry of dental school. Private practitioners also referred some patients. The study protocol was approved by the research ethics committee of the office of research of the University of Costa Rica, and each participant provided written informed consent. Family pedigrees and genetic information was entered into computer software using the Cyrillic program. Data was extracted from clinical records of the University of Costa Rica dental school, and direct family histories were obtained from the subjects. Data was organized in Punnett Squares, and analysis performed according to Mendelian Laws. Analysis of the pathological manifestation of Amelogenesis Imperfecta according to recessive, dominant or indeterminate patterns enabled a more precise determination of the likelihood of heritability in future generations. The results lead to a better understanding of the origin of this enamel condition and explain better its heritability to next generations of the same families. In order to confirm the precise genetic mutation(s) it is essential to collect and analyze DNA from saliva or blood of each subject. This is an additional line of research, not included within the scope of this text.